CD137 and PD-L1 targeting with immunovirotherapy induces a potent and durable antitumor immune response in glioblastoma models - Hong Jiang; Sandra Hervás-Stubbs; Sara Labiano; Candelaria Gomez-Manzano; Juan Fueyo; Marta Alonso; Zhihong Chen; Montserrat Puigdelloses; Marc Garcia-Moure; Virginia Laspidea; Marisol Gonzalez-Huarriz; Marta Zalacain; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Glioblastoma (GBM) is a devastating primary brain tumor with a highly immunosuppressive tumor microenvironment, and treatment with oncolytic viruses (OVs) has emerged as a promising strategy for these tumors. Our group constructed a new OV named Delta-24-ACT, which was based on the Delta-24-RGD platform armed with 4-1BB ligand (4-1BBL). In this study, we evaluated the antitumor effect of Delta-24-ACT alone or in combination with an immune checkpoint inhibitor (ICI) in preclinical models of glioma.Methods The in vitro effect of Delta-24-ACT was characterized through analyses of its infectivity, replication and cytotoxicity by flow cytometry, immunofluorescence (IF) and MTS assays, respectively. The antitumor effect and therapeutic mechanism were evaluated in vivo using several immunocompetent murine glioma models. The tumor microenvironment was studied by flow cytometry, immunohistochemistry and IF.Results Delta-24-ACT was able to infect and exert a cytotoxic effect on murine and human glioma cell lines. Moreover, Delta-24-ACT expressed functional 4-1BBL that was able to costimulate T lymphocytes in vitro and in vivo. Delta-24-ACT elicited a more potent antitumor effect in GBM murine models than Delta-24-RGD, as demonstrated by significant increases in median survival and the percentage of long-term survivors. Furthermore, Delta-24-ACT modulated the tumor microenvironment, which led to lymphocyte infiltration and alteration of their immune phenotype, as characterized by increases in the expression of Programmed Death 1 (PD-1) on T cells and Programmed Death-ligand 1 (PD-L1) on different myeloid cell populations. Because Delta-24-ACT did not induce an immune memory response in long-term survivors, as indicated by rechallenge experiments, we combined Delta-24-ACT with an anti-PD-L1 antibody. In GL261 tumor-bearing mice, this combination showed superior efficacy compared with either monotherapy. Specifically, this combination not only increased the median survival but also generated immune memory, which allowed long-term survival and thus tumor rejection on rechallenge.Conclusions In summary, our data demonstrated the efficacy of Delta-24-ACT combined with a PD-L1 inhibitor in murine glioma models. Moreover, the data underscore the potential to combine local immunovirotherapy with ICIs as an effective therapy for poorly infiltrated tumors.